Numerical wear study of metal‐on‐ultrahigh molecular weight polyethylene‐based cervical total disc arthroplasty by coupling finite element analysis and multi‐body dynamics. Issue 4 (8th October 2021) - Xin, Hua; Zhang, Lei; Diao, Hao; Jia, Junhong; Jin, Zhongmin
Abstract: In this study, the effects of in vivo (head flexion‐extension, lateral bending, and axial rotation) and in vitro (ISO 18192‐1) working conditions on the wear of ultrahigh molecular weight polyethylene (UHWMPE)‐based cervical disc prosthesis were studied via numerical simulation. A finite‐element‐based wear prediction framework was built by using a sliding distance and contact area dependent Archard wear law. Moreover, a pre‐developed cervical spine multi‐body dynamics model was incorporated to obtain the in vivo conditions. Contact mechanic analysis stated that in vitro conditions normally led to a higher contact stress and a longer sliding distance, with oval or crossing‐path‐typed sliding track. In contrast, in vivo conditions led to a curvilinear‐typed sliding track. In general, the predicted in vivo wear rate was one order of magnitude smaller than that of in vitro. According to the yearly occurrence of head movement, the estimated total in vivo wear rate was 0.595 mg/annual. While, the wear rate given by the ISO standard test condition was 3.32 mg/annual. There is a significant impact of loading and kinematic condition on the wear of UHMWPE prosthesis. The work conducted in the present study provided a feasible way for quantitatively assessing the wear of joint prosthesis.